Contractual justice in Asean: a comparative view of coercion - Shaik Mohd. Hussain, Shaik Md. Noor Alam (2002)
The European legal system which provided Indonesia, Thailand and partly Philippines with much of their ground rules in contract has witnessed a new and rapidly increasing awareness of the need for justice in contract. Hence, countries sharing the same European legal tradition are well placed to embark on a similar path towards contractual justice. British legal tradition, of which Malaysia is a part, places an undue and unfortunately illusory emphasis on freedom of contract. Free and voluntary consent must be looked at as a mechanism to achieve contractual justice not contractual freedom. An examination of coercion in several ASEAN jurisdictions will reveal the need for this distinction .